Dilated perivascular spaces can present incidental CSF-isointense foci within the ventral forebrain of dogs and cats in transverse MR images - Fischer, Carolin; Schaub, Sebastian; Büttner, Kathrin; Hartmann, Katinka; Schmidt, Martin Jürgen (Frontiers in Veterinary Science, 2022)
Objective: Virchow-Robin-Spaces (VRS) are cerebrospinal fluid (CSF)-containing perivascular spaces encompassing brain vessels while coursing through the parenchyma. VRS can enlarge and become visible in magnetic resonance imaging (MRI). While dilatated VRS are mostly incidental findings, they were associated with degenerative brain disease in humans. This study aimed to evaluate their occurrence and MRI morphology within the ventral forebrain of structurally normal canine and feline brains and physiological cerebrospinal fluid analysis. Sample: Retro- and prospective, observational study reviewing medical records of client-owned dogs and cats who underwent MRI brain scans for unrelated reasons between 2011 and 2021. We comprised studies with various magnetic field strengths (1 Tesla/3 Tesla). Out of 2500 brain scans, three hundred thirty-five patients (293 dogs, 42 cats) presented with absent intracranial pathology and physiological CSF analysis and were included. Procedure: The ventral forebrain of the included animals was assessed for bi- or unilateral CSF-isointense foci in the transverse plane. Statistical correlations were evaluated between dilated VRS presence, field strength, age, gender, weight, and cranium conformation. Additionally, a post-mortem histopathologic analysis of one dog and one cat showing dilated VRS on MRI was performed to confirm perforating arteries in the grey matter of the ventral forebrain. Results: 57% of patients presented dilated VRS (N=191: 170 dogs, 21 cats). 43% did not display dilated VRS (control group; N=144: 123 dogs, 21 cats). A significant relation between increased magnetic field strength and detection of dilated VRS was observed in dogs; there was a 2,4 increase (p=0,0001) in detection using 3 Tesla vs 1 Tesla. There was a 2,4-fold increase in dilated VRS occurrence in male dogs compared to female dogs. Detection also increased with the rise of body weight. We detected no statistically significant difference between dilated VRS and the control group in age, species or cranium conformation. Conclusion and Clinical Relevance: Dilated VRS can be seen within the ventral forebrain at the level of the rostral commissure on transverse MR images as symmetrical or unilateral, dot-like, CSF-isointense areas. Understanding their signal intensity features and localization prevents misinterpretation and helps differentiate them from various pathological conditions.